Development of an HPLC Method for Simultaneous Determination of Chlorogenic Acid, Cryptochlorogenic Acid, Rutin, and Isoquercitrin in Leaves of Morus alba - Thi Minh Diep, Nguyen; Thi Thu Huong, Kieu; Thanh Hoa, Ha; Thi Van Anh, Tran; Thanh Hai, Nguyen; Thi Mai Huong, Phi; Van Thang, Nguyen; Tuan, Pham Quoc (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4DO - 10.25073/2588-1132/vnumps.4800, 2025)
Abstract: An HPLC-DAD method was developed for the simultaneous quantification of four main substances in leaves of Morus alba , including chlorogenic acid, cryptochlorogenic acid, rutin, and isoquercitrin. The method was executed on a Phenomenex C18 column (250 × 4.6 mm, 5 µm) with a mobile phase solvent system of acetonitrile and 0.1% formic acid in water, eluted according to a gradient program. The flow rate was maintained at 0.85 mL/min, with an injection volume of 10 µL. Detection wavelengths were set at 324 nm for chlorogenic acid and cryptochlorogenic acid, and 353 nm for rutin and isoquercitrin. This analytical method was validated and met the requirements according to the ICH guidelines on specificity, system suitability, linearity range, precision, and accuracy. The established method was applied to determine the content of eight leaf samples of Morus alba collected from Phu Tho and Ha Noi. The results indicated that the average content of chlorogenic acid, cryptochlorogenic acid, rutin, and isoquercitrin in these samples was 11.96 - 12.72, 1.81 - 2.63, 1.66 - 1.81, and 6.09 - 6.29  mg/g based on dry leaf weight, respectively. Keywords: Chlorogenic acid, cryptochlorogenic acid, rutin, isoquercitrin, HPLC, Morus alba leaves.